Arboviruses: A global public health threat. Issue 24 (19th May 2020) - Girard, Marc; Nelson, Christopher B.; Picot, Valentina; Gubler, Duane J.
Abstract: A conference on «ARBOVIRUSES, A GLOBAL PUBLIC HEALTH THREAT» was organized on June 20–22, 2018 at the Merieux Foundation Conference Center in Veyrier du Lac, France, to review and raise awareness to the global public health threat of epidemic arboviruses, and to advance the discussion on the control and prevention of arboviral diseases. The presentations by scientists and public health officials from Asia, the Americas, Europe and Africa strengthened the notion that arboviral diseases of both humans and domestic animals are progressively becoming dominant public health problems in the world. The repeated occurrence of recent deadly epidemics strongly reinforces the call for action against these viral diseases, and the need for developing effective vaccines, drugs, vector control tools and strong prevention programs.